Effects of dietary arginine silicate inositol complex on mineral status in rainbow trout (Oncorhynchus mykiss) - Kucukbay, F. Z.; Yazlak, H.; Şahin, Nurhan.; Akdemir, F.; Orhan, C.; Juturu, V.; Şahin, Kazım (Wiley, 2008)
Arginine silicate inositol complex (ASI; arginine 49.47 g kg(-1), silicon 8.2 g kg(-1), inositol 25 g kg(-1)), a novel composition that is a bioavailable source of silicon and arginine, has potential benefits for vascular and bone health. We have previously reported that bone mineral content increased and the amount of Ca, P, Mg and Mn in the excreta decreased in poultry with ASI supplementation. In the present study, the effect of ASI supplementation at various levels (0, 500, 1000 mg kg(-1) ASI) on growth, feed intake, feed conversion ratio (FCR) and concentrations of body elements, operculum bone ash and activity of serum alkaline phosphatase (ALP) in rainbow trout was evaluated. Ninety 0+ year-old rainbow trout with initial average weight of 50 +/- 3 g were randomly assigned to three treatment groups, three replicates of 10 fish each. The fish were fed either a basal diet or the basal diet supplemented with either 500 or 1000 mg of ASI. Body weight gain (P = 0.25), feed intake (P = 0.36) and feed efficiency (P = 0.42) were not signifcantly influenced by the dietary ASI supplementation. Per cent operculum bone ash (634 g kg(-1) versus 558 g kg(-1), P = 0.001) and ALP activity (112 UL-1 versus 92 UL-1, P = 0.001) linearly increased as dietary ASI supplementation increased. Increasing dietary ASI supplementation linearly increased serum and whole body Ca (P = 0.01), P (P = 0.01), Mg (P = 0.05; P = 0.001) Mn (P = 0.05; P = 0.01) and Zn (P = 0.01; P = 0.02) concentrations respectively. In conclusion, ASI supplementation to the basal diet significantly improved operculum bone ash and whole body mineral content in rainbow trout and did not impact feed consumption, weight gain or FCR.
Keywords: alkaline phosphatase; arginine silicate inositol; bone; minerals; rainbow trout